1994
DOI: 10.1111/j.1440-1754.1994.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in oxygen saturation over the first year of life: A longitudinal study

Abstract: Stability of oxygen saturation depends on maturation and function of individual components of the respiratory system. The aim of this study was to record and analyse comprehensive oxygen saturation data in a longitudinal study over the first year of life. Detailed sleep studies were performed on 15 normal infants eight times in the first year of life. The accrued oxygen saturation data were analysed on a computerized oximetry data analysis system. Results show the mean sleep saturation levels trending upwards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
3
17
0
1
Order By: Relevance
“…Since its introduction, numerous studies have shown the pulse oximeter to be accurate and reliable in neonates. [1][2][3][4][5][6] Normative ranges for pulse oximetry saturation in children [7][8][9] and adults 10 have been well established. In contrast, normal pulse oximetry saturations have not been well established for healthy term newborn infants in the first hours and days of life.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction, numerous studies have shown the pulse oximeter to be accurate and reliable in neonates. [1][2][3][4][5][6] Normative ranges for pulse oximetry saturation in children [7][8][9] and adults 10 have been well established. In contrast, normal pulse oximetry saturations have not been well established for healthy term newborn infants in the first hours and days of life.…”
Section: Introductionmentioning
confidence: 99%
“…The median baseline SpO 2 in healthy term infants during the 1st year of life is 97–98% 7. There have been two longitudinal studies of SpO 2 in infants over their first 6–12 months, one showed a slight increase with age,8 the other found no increase in baseline but did see a reduction in variability 9. Certainly if the baby has a low SpO 2 , the urgency of the situation and need for further investigations are heightened; our cut-off for immediate action is 94% or below.…”
Section: Immediate Clinic Investigationsmentioning
confidence: 99%
“…Masters et al 4 found a slight increase in baseline levels with age but, in contrast, Hunt et al 3 found no change in baseline with age but a decrease in variability. The five infant studies from the Stoke group59 used a modified oximeter, operating in a beat-to-beat mode (not available for clinical use), and restricted analyses of oxygen baselines to periods of regular breathing (table 1).…”
Section: Introductionmentioning
confidence: 95%
“…The mean percentage of time spent <90% has been reported in three studies of term infants,3 4 14 and ranges from 0% to 2%; in preterm babies it was approximately 2.5% 11. However, the 95th centile of the time spent <90% was 0.1–4% in term babies14 and approximately 11.5% in preterm babies 11…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation